The Effects of Carbon and Plastic Ankle-Foot Orthoses on Gait, Balance, and Mobility in Persons with Multiple Sclerosis: A Pilot Study. Issue 3 (9th July 2021) - Jackson, Kurt; Bigelow, Kimberly Edginton; Hollis, Sarah
ABSTRACT: Introduction: Ankle-foot orthoses (AFOs) are commonly prescribed to improve gait in individuals with multiple sclerosis (MS). However, there is currently little research to support their use or guide clinicians in the prescription process in this population. The purpose of this pilot study was to compare the effects of carbon and plastic AFOs on measures of gait, balance, and mobility in persons with MS. Materials and Methods: Ten individuals with MS who had not used an AFO previously had their gait, balance, mobility, and perception of benefit assessed under three different AFO conditions: no AFO, carbon AFO (C-AFO), and plastic AFO (P-AFO), on separate days. Gait was assessed using an instrumented 10-m walk, a 6-minute walk, the physiological cost index (PCI), and a visual analog fatigue rating scale. Static balance was assessed using posturography under different sensory conditions and dynamic balance using the limits of stability (LOS) test. Mobility was assessed using the timed up and go (TUG) test. The perceived benefit of using the AFO was measured with an eight-item Likert scale survey. Results: No significant differences were identified between the C-AFO and P-AFO conditions for any of the gait, balance, and mobility measures. Both AFO types tended to improve static balance but negatively impacted dynamic balance and mobility when compared with no AFO. There was no significant difference in the perceived benefit between the AFO types. However, there were differences in the PCI and perception of benefit for individual subjects that could be clinically meaningful. Conclusions: There were no differences in gait, balance, and mobility measures or perception of benefit between C-AFO and P-AFO in persons with MS. However, there were differences in individual performance that may warrant consideration when prescribing AFOs. Therefore, clinicians should consider using appropriate standardized assessment tools that measure various aspects of gait, balance, and mobility when evaluating individual responses to AFOs.